2020
DOI: 10.1038/s41598-020-68924-0
|View full text |Cite
|
Sign up to set email alerts
|

Surface Water CO2 variability in the Gulf of Mexico (1996–2017)

Abstract: Approximately 380,000 underway measurements of sea surface salinity, temperature, and carbon dioxide (co 2) in the Gulf of Mexico (GoM) were compiled from the Surface Ocean CO 2 Atlas (SOCAT) to provide a comprehensive observational analysis of spatiotemporal CO 2 dynamics from 1996 to 2017. An empirical orthogonal function (EOF) was used to derive the main drivers of spatial and temporal variability in the dataset. In open and coastal waters, drivers were identified as a biological component linked to riverin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 68 publications
1
14
1
Order By: Relevance
“…Along the coast, inputs of fresh water (decrease in salinity and increase in CO 2 solubility) and nutrients (biological activity and DIC drawdown) combine to strengthen CO 2 uptake (Arrigo et al, 2010;Yasunaka et al, 2016;Olafsson et al, 2021). uptake is also found over the western continental shelf where strong river discharges sustain high levels of biological productivity in particular during spring (Jamet et al, 2007;Kealoha et al, 2020). Weaker sinks or sources of CO 2 in the southwestern StA and the eastern subtropical gyre are primarily driven by high surface temperature and enhanced stratification .…”
Section: Atlanticmentioning
confidence: 99%
“…Along the coast, inputs of fresh water (decrease in salinity and increase in CO 2 solubility) and nutrients (biological activity and DIC drawdown) combine to strengthen CO 2 uptake (Arrigo et al, 2010;Yasunaka et al, 2016;Olafsson et al, 2021). uptake is also found over the western continental shelf where strong river discharges sustain high levels of biological productivity in particular during spring (Jamet et al, 2007;Kealoha et al, 2020). Weaker sinks or sources of CO 2 in the southwestern StA and the eastern subtropical gyre are primarily driven by high surface temperature and enhanced stratification .…”
Section: Atlanticmentioning
confidence: 99%
“…The rate and magnitude of OA at the FGB are unknown over the period covered by our cores. The threat of OA in the northwest Gulf of Mexico is poorly understood because seawater carbonate chemistry is influenced by the interplay of varying river discharge and the complex hydrodynamics of this region (Kealoha et al 2020b). Over the 10-yr period from 2007 to 2017, Hu et al (2018) reported a rate of OA at FGB that was greater than what has been measured in the Hudson and Robbin (1981) and Dodge and Lang (1983) D, Growth declines/anomalies associated with periods of high Atchafalaya discharge (1973-75, 1983-85, 1990-91, 1994, 1998, 2009-11).…”
Section: Pseudodiploria Strigosamentioning
confidence: 99%
“…Includes period from 1964 to 1970 that saw a rapid increase in Atchafalaya discharge ?, Growth anomalies that are not associated with a known event or environmental factor Coral Reefs open ocean. However, just to the east in the central regions of the open-ocean and coastal portion of the Gulf of Mexico, there has been no long-term trend in surface pCO 2 , SST, or salinity (Kealoha et al 2020b). The impact of runoff from the Mississippi and Atchafalaya Rivers can effectively erase any OA signal because runoff impacts surface productivity, as well as directly modifies seawater chemistry, both of which introduce variability that makes a long-term OA signal difficult to detect.…”
Section: Pseudodiploria Strigosamentioning
confidence: 99%
“…The GOM estuaries currently have less exposure to concerning levels of acidification than other estuaries because of their high temperatures (causing water to hold less CO 2 and support high productivity year-round) and often suitable river chemistries (i.e., relatively high buffer capacity) (McCutcheon et al, 2019;Yao et al, 2020). However, respiration-induced acidification is present in both the open GOM (e. g., subsurface water influenced by the Mississippi River Plume and outer shelf region near the Flower Garden Banks National Marine Sanctuary) and GOM estuaries, and most estuaries in the northwestern GOM have also experienced long-term acidification (Cai et al, 2011;Hu et al, 2015Hu et al, , 2018Kealoha et al, 2020;Mc-Cutcheon et al, 2019;Robbins and Lisle, 2018). This evidence of acidification as well as the relatively high CO 2 efflux from the estuaries of the northwest GOM illustrates the necessity to study the baseline variability and driving factors of carbonate chemistry in the region.…”
Section: Introductionmentioning
confidence: 99%